Who isn't that masked man: The absence of re-authoring in The Lone Ranger. Issue 2 (1st June 2014) - Moll, Nicholas
From its radio debut in 1933 through to the 2013 film, The Lone Ranger (TLR) franchise has continued to grow, expanding from these beginnings into television, novel, comic books and, as noted, film. With the expansion of TLR still a continuing, albeit occasionally dormant, process, the franchise itself possesses a broad history filled not only with additions but also absences. This article is concerned with one absence in particular with: re-authoring. Other media franchises featuring popular Superheroes typically delved, with varying degrees of frequency, into re-authored variants of their canonical narrative – producing distinct images and varied ideas surrounding their characters. Yet, TLR has remained squarely within a pseudo-historical nineteenth-century-western United States and concerning an ambushed Texas Ranger who becomes a masked vigilante-Superhero – and it is this absence that marks TLR as distinct compared with other long-running media franchise texts. Through history along with media and genre theory, this article explores the history and character of TLR retrospectively, focusing on the absence of setting and genre variation in contrast to the use and theme of the Frontier throughout the franchise. Within this exploration we position the figure of the masked man as Superhero surrounded by the history of the American West, attributing the absence of re-authoring to this arrangement, seeing the notion of the masked man entrenched rigidly into ideas surrounding the nineteenth century westward expansion of the United States.